Pengelolaan Tata Usaha dalam Peningkatan Pelayanan Administrasi di MTs Al-Asna Barat - Khasana, Imroatul; Nurul Laili Herzegovina, Rani (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The purpose of this study is to examine how MTs Al-Asna Barat's administration is managed in order to enhance administrative services, as well as to pinpoint challenges and potential solutions.  The research employs a descriptive qualitative methodology, gathering data via observations, interviews, and documentation.  According to the study's findings, effective administrative management can boost service effectiveness, increase the correctness of paperwork, and fortify the madrasah management level's decision-making process. Delays in document collecting, inadequate archival facilities, and a lack of digitization are the primary challenges. Implementing an information technology-based administration system, enhancing HR competencies, and modifying work systems are some of the tactics used. This study emphasizes how crucial it is to manage school administration by putting quality management principles, transformational leadership, and digital system integration into practice. These results have ramifications for how educational institutions can create administrative policies that are flexible and responsive to the times.